In Vivo Biomechanical Changes Associated With Keratoconus Progression. (3rd July 2022) - Padmanabhan, Prema; Lopes, Bernardo T.; Eliasy, Ashkan; Abass, Ahmed; Elsheikh, Ahmed
Abstract: Purpose: To assess the biomechanical deterioration arising from keratoconus progression in-vivo . Methods: The preoperative examinations of 32 progressive KC cases that were submitted to corneal cross-linking were evaluated. The examinations included the corneal tomography using the Pentacam HR and biomechanical parameters assessed by the Corvis ST (Oculus, Wetzlar, Germany). The results were recorded at two time points, the latter of which was at the last visit before the CXL procedure. Keratoconus progression was characterised by a significant change in the ABCD system. Results: At the last follow-up visit (41.4 ± 40.9 months) all morphological parameters of the ABCD grading system showed significant deterioration ( p < 0.001). The comparative analyses revealed a significant reduction in corneal stiffness expressed by a significant reduction in the stress-strain index (SSI: −0.10 ± 0.06, p < 0.001), the Stiffness parameter A1 (SP-A1: −6.1 ± 12.0 mmHg/mm, p = 0.011), by a significant increase in the integrated Inverse Radius (IIR: 0.95 ± 1.04 mm-1, p < 0.001) and in the deflection amplitude (DA) ratio (0.23 ± 0.58, p = 0.034). A barely significant increase in the DA also pointed towards corneal stiffness reduction. (0.04 ± 0.13 mm, p = 0.056). The SSI and the IIR were the indices with the smallest overlaps between the two examinations. Conclusions: It has been demonstrated in-vivo that corneal biomechanical deterioration occurs with keratoconus progression. The larger changes observed in the SSI and the IIR when compared to the remaining biomechanical parameters suggests that these parameters could be suitable to assess the corneal stiffness reduction in keratoconus natural progression.